Study of Bone Mineral Density in Transfusion Dependent Thalassemia, its correlation with Biochemical and Hematological parameters: A Cross-Sectional Study - Hegde, Darshan; Ghildiyal, Radha; Sharma, Sujata; Zope, Sadhana; K M, Manavi; Ramaswamy, Manjunath (Pediatric Review: International Journal of Pediatric Research, 2024)
Background: In thalassemic patients, bone disease is an important cause of morbidity. Patients with transfusion-dependent thalassemia (TDT) are susceptible to osteopenia and osteoporosis, the mechanism being multi-factorial. The present study was undertaken to study the prevalence of osteopenia and osteoporosis in TDT patients and describe its correlation with biochemical, hematological profile. Method: A total of 84 patients with TDT on regular PRC transfusion and iron chelation therapy aged between 5-18years were enrolled in the study. Bone mineral densities (BMD) was measured by DXA scan (DXA spine/whole body) and categorized into normal, osteopenia and osteoporosis based on WHO grading system. Results: Out of 84 subjects, 57.1% had low BMD with 38(45.2%) having osteopenia and 10(11.9%) of them having osteoporosis. The prevalence of osteoporosis was found to be more by DXA Spine than DXA whole body which was found to be statistically significant (P=0.043). A high prevalence of hypoparathyroidism, hypocalcemia, hypovitaminosis D and increased serum phosphorous levels were noted among TDT patients with low BMD. Iron overload in Myocardium by T2*MRI also showed statistically significant association with low BMD as determined by DXA Spine. Conclusion: Low bone mass is one of the most prevalent complications among TDT patients. Osteoporosis is a progressive disease with multifactorial etiology. Iron overload status by T2* Cardiac MRI may be used as an early indicator for predicting Osteoporosis along with T-scores from DXA spine for early diagnosis and interventions. Further longitudinal prospective studies are needed to better understand the etiopathogenesis of bone disease in these patients.